Foreseeing the complex network of relationships and interactions of the brazilian community health care agent - Gabriela Marcelino de Melo Lanzoni; Betina Horner Schlindwein Medeiros (Rev Rene)
The objective of this research was to understand the meaning of the network of relationships and interactions of Community Health Care Agents (CHCA) and a Local Health Care Unit in Florianópolis/SC. The Grounded theory was used as a methodological reference. Data were collected between February and April 2009, through interviews with CHCA, nurses, doctors and dentists, divided into three sample groups, totaling 20 participants. The data analysis emerged the phenomenon foreseeing the relationships and interactions of the CHCA in improving care for users as a complex network, composed of the inter-relationship of six categories. The network of relationships and interactions of the CHCA is a unit that, serving as the care process facilitator between health care and the community, composes the “health” system. The Nurse is the professional who directly interferes in the CHCA relationship with the team, because he mediates communication, integrates people and articulates knowledge.